The political, social and economic situation of the leader under the Umayyad state - كانبي, صالح; كريم, بختیار عبد الله (Sulaimani Journal for Humanities, 2019)
It could be said that Berbers (Amazighs) are one of the nations that confronted the Islamic expansion for a long time. Islamic conquest of the territories of the Berbers continued from 643 to 709 AD (21-90 AH). Most of the conquests occurred during the Umayyad era. Therefore, the situation of the Berbers and officials and commanders of the Umayyad Caliphate’s perspectives on the Berbers were not different from the perspective which existed during the Islamic expansion. This led to the unity of the Berber tribes against the Umayyad Caliphate regardless of disputes and enmities which the tribes had with each other. They struggled to liberate their territories under the Umayyad Caliphate, and they were finally able to liberate most of their region under the name of the Khawarij sect. This study discusses the economic and humanitarian situations of the Berber nation under the Umayyad’s rule, and it also shows the oppressive policies of the some of the Umayyad rulers. It is divided into two chapters. The first chapter illustrates the economic and humanitarian situations during (Musa Bin Nusair 705-715 AD, 86-96 AH). The second chapter evaluates the economic and humanitarian situations of the Berber nation under the continuous oppression of the Umayyad rulers and the responsibilities of the Umayyad Caliphs.